METAPHOR PLAY BETWEEN JOKOWI AND PRABOWO IN THE LAST BATTLE - Khristianto Khristianto; Arif Budiman (ELITE JOURNAL, 2019)
Metaphor is many times a spontaneous expression to pack a person’s feeling on a phenomenon. This is obvious in a political contest between Jokowi and Prabowo in the last presidential election in Indonesia. Both always exchange statements to respond over a thing or one to another. Their statements flower with the use of metaphors to represent and to emphasize their subjective perception. This research is a content analysis making use the texts from Indonesian media recording the statements of the two contestants. From the data source, the metaphor is selected and analyzed using theory of conceptual metaphor (Lakoff& Johnson: 1980) of which meanings are seen from CDA’s concept of Teun van Dijk (2001) and Lynne’s (2008) affective effect of metaphor. After the analysis, it was found out that the metaphor functions to emphasize the topics in question, like the importance of Indonesian unity as in “menjalin dan merawat…persaudaraan”, to distance the topics, “sedikit kesulitan”, and to evaluate positively, “kue ekononomi digital”. Both sides agree that unity is important, but they blame each other as being the culprit of the broken unity. In other issues, both sides make use of their opposing ideas to hyperbolize others’ negativity and to conceal others’ positivity.